Pemberdayaan Usaha Ekonomi Produktif Pada Masa Pandemi Covid-19 Bagi Masyarakat Leong Jaya Desa Giri Madia Kecamatan Lingsar Kabupaten Lombok Barat - Handry Sudiartha Athar; Prayitno Basuki; Lalu Edy Herman Mulyono (Unram Journal of Community Service, 2022)
The purpose of carrying out this Community Service activity is to foster an entrepreneurial spirit for the community through the formation of joint business groups during the Covid-19 Pandemic Period and empowering community potential in increasing family income through increasing productive economic businesses during the Covid-19 Pandemic Period. The strategic target audience in this activity is the community belonging to the Family Towards Prosperity (KMS) who are in Leong Jaya Hamlet, Giri Madia Village, Lingsar District. The number of training participants was 20 people consisting of men and women. Based on the results of the service activities, the Leong Jaya Community was very enthusiastic about this activity. They were excited because they received important information on how to improve their business selling palm wine, which they had been doing in the traditional way, selling directly to traditional markets. The local community hopes that this kind of activity will continue to be carried out so that they will find important information on how to improve their business for the better. What is really expected is how this sweet wine business can be marketed to the wider community in an easier way